Integrative genomic and transcriptomic approaches decipher pre-harvest sprouting resistance in rice - Yang, Lv; Yang, Renyuan; Wang, Yuxuan; Asad, Muhammad Asad Ullah; Wang, Yueying; Chang, Zhiyuan; Miao, Tianhui; Yang, Shudong; Wei, Yiting; Wu, Shanshan; Bao, Jiaxue; Wu, Mingming; et al. (Frontiers in Plant Science, 2025)
Pre-harvest sprouting (PHS) seriously compromises rice yield and quality, increase susceptibility to insect pest and reduce seed viability. Beside agronomic control measures, the genetic makeup of rice plants serves as a fundamental determinant in conferring resistance to PHS. Therefore, integrating multi-omics strategies to construct high-resolution genetic variation maps, screen extreme-phenotype germplasm, and identify causal genes are pivotal for generating PHS-resistant breeding material. In this study, we performed whole-genome re-sequencing of 165 highly diverse indica rice accessions to construct a high-density genetic variation map, obtaining a dataset comprising 1,584,905 high-quality SNPs for subsequent association analysis. Genome-wide association studies (GWAS) further uncovered 21 candidate loci and multiple candidate genes associated with PHS, from which key candidate genes were prioritized. In particular, previously cloned PHS-related genes—OsCDP3.10, OsWRKY50, UGT74J1, OsJAZ6, and IPA1. Additionally, we investigated the transcriptional analyses in cultivars Z33 and Z216 under high-humidity conditions and identified 19,087 differentially expressed genes (DEGs). Notably, by integrating GWAS and transcriptomic analyses, we identified UGT74J1 as a promising candidate gene, and haplotype analysis further revealed UGT74J1-Hap3 as a superior haplotype associated with PHS resistance. This multi-omics dataset and the candidate genes identified will provide valuable genetic resources for molecular breeding toward improved PHS resistance in rice.